Nonlinear effects of blue-green space variables on urban cold islands in Zhengzhou analyzed with random forest regression - Quan, Shu; Li, Maojuan; Li, Tianqi; Liu, Haodong; Cui, Yaohui; Liu, Miaohan (Frontiers in Ecology and Evolution, 2023)
Urban cold island effects have become increasingly relevant with accelerating climate change. However, the relationship between such effects and their causal variables remains unclear. In the present study, we analyzed the relationship between blue-green space variables and land surface temperature (LST) and park cooling intensity (PCI) in central Zhengzhou City using a random forest regression model. Cool urban areas corresponded to the location of blue-green spaces. The average temperatures of these spaces were 2 ℃ and 1 ℃ lower than those of the built-up areas and the full study region, respectively. Blue-green spaces also had a maximum temperature that was 8 ℃ lower than those of the built-up areas and the study region. The three primary variables determining LST were blue space proportion and area and vegetation cover, whereas the three variables determining PCI were blue-green space width, vegetation cover, and patch density. At a width of 140 m, blue-green spaces caused a PCI peak, which further improved at 310 m. The proportion of blue space had a stepwise effect on PCI. A vegetation coverage of 56% represented the lower threshold of LST and the higher threshold of PCI. These results reflect a nonlinear relationship between blue-green variables and urban cold islands. In conclusion, the study provides data that could inform the efficient use of blue-green spaces in urban construction and renewal.